Management challenges and work passion of school instructional leaders in the new Philippine setting - Ma. Viczie Tubongbanua; Evangeline Ybañez (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
The pandemic instigated eighty percent of world’s children and youth to be out of school posing management challenges among school leaders. This study sought to determine the extent of management challenges and the level of work passion of school instructional leaders (SILs) in the province of Capiz under the new framework and plan of action during the school year 2020-2021. The descriptive survey correlational research design and stratified sampling were used. A researcher-made questionnaire was used to gather data from 222 SILs in the province of Capiz as respondents. The statistical tools used to analyze and interpret data were frequency count, percentage, mean, t-test, Analysis of Variance and Pearson r. The level of significance was set at 0.05 alpha. The results revealed that SILs were challenged in terms of management and were remarkably passionate in their work. The extent of management challenges and the level of work passion of school instructional leaders varied in educational qualification and length of service. Demographic profile as to sex, age, and school category did not affect the extent of management challenges and the level of work passion of SILs. Furthermore, the extent of management challenges was significantly related to the level of work passion of the SILs.